The multiple roles of GH in neural ageing and injury - Blackmore, Daniel G.; Waters, Michael J. (Frontiers in Neuroscience, 2023)
Advanced age is typically associated with a decrease in cognitive function including impairment in the formation and retention of new memories. The hippocampus is critical for learning and memory, especially spatial learning, and is particularly affected by ageing. With advanced age, multiple neural components can be detrimentally affected including a reduction in the number of neural stem and precursor cells, a decrease in the formation of adult born neurons (neurogenesis), and deficits in neural circuitry, all of which ultimately contribute to impaired cognitive function. Importantly, physical exercise has been shown to ameliorate many of these impairments and is able to improve learning and memory. Relevantly, Growth hormone (GH) is an important protein hormone that decreases with ageing and increases following physical exercise. Originally described due to its role in longitudinal growth, GH has now been identified to play several additional key roles, especially in relation to the brain. Indeed, the regular decrease in GH levels following puberty is one of the most well documented components of neuroendocrine ageing. Growth hormone deficiency (GHD) has been described to have adverse effects on brain function, which can be ameliorated via GH replacement therapy. Physical exercise has been shown to increase circulating GH levels. Furthermore, we recently demonstrated the increase in exercise-mediated GH is critical for improved cognitive function in the aged mouse. Here we examine the multiple roles that GH plays, particularly in the aged brain and following certain types of injury, and how increasing GH levels can ameliorate deficits in cognitive health.